Climate trends, risks and coping strategies in smallholder farming systems in Uganda - Mubiru, D.N.; Radeny, Maren A.O.; Kyazze, Florence Birungi; Zziwa, A.; Lwasa, J.; Kinyangi, J.; Mungai, C. (Elsevier, 2018)
Smallholder farmers in Uganda face a wide range of agricultural production risks. Climate change and variability present new risks and vulnerabilities. Climate related risks such as prolonged dry seasons are becoming more frequent and intense with negative impacts on agricultural livelihoods and food security. This paper examines farmers' perceptions of climate change, climate-related risks affecting crop and livestock production, including climate-risk management and adaptation strategies. Percieved changes in climate included erratic rainfall onset and cessation (which were either early or late), poor seasonal distribution of rainfall and decreased rainfall. In addition, farmers reported variations in temperatures. Drought, increasing disease and pest incidences, decreasing water sources, lack of pasture, bush fires, hailstorms, changes in crop flowering and fruiting times were the major climate-related risks reported. In order to cope with climate change and climate variability, farmers use a wide range of agricultural technologies and strategies. Mulching, intercropping and planting of food security crops were among the most commonly used practices. Other strategies included water harvesting (mainly for domestic consumption), other soil and water conservation technologies and on-farm diversification. Farmers often use a combination of these technologies and practices to enhance agricultural productivity. Analysis of trends in temperature and rainfall showed an increase in average maximum temperatures, while average annual rainfall showed mixed results, where a general decline was observed in one district and a relatively stable trend in the other district. Farmers' perception of changing rainfall characteristics and increasing temperatures were consistent with observed historical climatic trends based on meteorological data.